Phenotypic signatures and genetic determinants of oxacillin tolerance in a laboratory mutant of staphylococcus aureus - Chung, Marilyn (2019)
Addition of β-lactam antibiotics to growing cultures of bacteria inhibit synthesis of the bacterial cell wall peptidoglycan accompanied by killing (loss of viable titer) and lysis (physical disintegration) of the cells. However, it has also been well established that these antibiotics are not effective in killing non-growing or slow-growing bacteria and the mechanism of this “antibiotic tolerance” is not well understood. In this study, we report on the genetic basis and phenotypic properties of an antibiotic tolerant derivative of the methicillin susceptible S. aureus strain 27s. Cultures were exposed to “pulses” of high concentrations of oxacillin followed by outgrowth of the surviving bacteria. This procedure quickly selected for antibiotic tolerant mutants with an increased ability to survive antibiotic treatment without increase in the MIC value for the antibiotic. Such mutants also exhibited longer lag phase, decreased lysis, virtually no change in antibiotic susceptibilities, cross tolerance to D-cycloserine and vancomycin, and increase in biofilm formation in the presence of high concentrations of oxacillin. Whole genome sequencing showed that these altered properties were linked to mutations in the atl and gdpP genes.